ADVANTAGES OF USING 3D STUDIO MAX FOR CONDUCTING CHEMICAL EXPERIMENTS - Sarimova Dildora Soatalievna (Galaxy International Interdisciplinary Research Journal, 2021)
The basis of a modern education system is quality and high creates a technological environment. Its creation and development technically complex, as well as training in such an environment to improve the system, information communication in the educational process serves to introduce technologies. Education in the process the use of multimedia technologies interactive lessons mode. The basis of a modern education system is quality and high creates a technological environment. Its creation and development technically complex, as well as training in such an environment to improve the system, information communication in the educational process serves to introduce technologies.